Study Of Air Fuel Ratio On Engine Performance Of Direct Injection Hydrogen Fueled Engine - M. M., Rahman; M. M., Noor; M. R. M., Rejab; M. S. M., Sani; K., Kadirgama (2008)
The present study focuses on the effect of air-fuel ratio on the performance of four cylinder hydrogen fueled direct injection internal combustion engine. GT-Power was utilized to develop the model for direct injection engine. Air-fuel ratio was varied from rich to a lean limit. The rotational speed of the engine was varied from 1250 to 4500 rpm. The acquired results shown that the air fuel ratio are greatly influence on the brake mean effective pressure (BMEP), brake efficiency (BE), brake specific fuel consumption (BSFC) as well as the maximum cylinder temperature. It can be seen that the decreases of BMEP, BE and maximum cylinder temperature with increases of air fuel ratio and speed, however, increases the brake specific fuel consumption. For rich mixtures (low AFR), BMEP decreases almost linearly, then BMEP falls with a non-linear behavior. It can be observed that the brake thermal efficiency is increases nearby the richest condition (AFR ≅ 35) and then decreases with increases of air fuel ratio. Maximum b η of 35.4% at speed 2500 rpm can be seen compared with 26.3% at speed 4500 rpm. The optimum minimum value of BSFC occurred within a range of AFR from 38.144 ( 9 . 0 = θ ) to 49.0428 ( 7 . 0 = θ ) for the selected range of speed. The present contribution suggests the direct injection fuel supply system as a strong candidate for solving the power and abnormal combustion problems.